The Analysis of The Effects of Earning Per Share, Price Earning Ratio and Dividend Per Share on The Share Prices of Manufacturing Companies - Sundoro, Fredericho Mego; Anggraini, Yuyun; Pradiptya, Adhi (Economics and Business Solutions Journal, 2023)
The research analyzed the effect of earnings per share, price earnings ratio, and dividend per share on the share prices of manufacturing companies listed on the Indonesian Stock Exchange 2018-2021. The hypothesis of this study is earning per share, price earnings ratio, and dividend per share positive effect on the share prices of manufacturing companies listed on the Indonesia stock exchange in 2018-2021.  The number of samples in this study was 60 manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021 using the sampling technique of purposive sampling. The data collection method used documentation, and the data analysis used the SPSS which included classic assumption test, multiple linear regression analysis, and hypothesis testing using t-test, F and R test2..  The results of the study show as follows: the independent variable of earning per share has a positive effect on the share prices; the price earnings ratio has a positive effect on the share prices; and the dividend per share does not have an effect on the share prices. Based on the values of the coefficient of determination, the test results show an Adjusted R square value of 0.266. It means that a change in the share price variable of 26.6% can be explained using the three independent variables (Earning Per Share (EPS), Price Earnings Ratio (PER), and Dividend Per Share (DPS). Then, the remaining 73.4% is explained by the other variables out of the independent variables such as net interest margin, net profit margin, and debt to asset ratio.